Edible Weeds in Paddy (Oryza sativa L.) Fields of Sivagangai District in Tamilnadu, India - Shanmugam, S.; Selvakumar, P.; Annadurai, M.; Rajendran, K. (Indian Forester, 2012)
Occurrence of 19 weeds (18 angiospermic and 1 pteridophytic weed) was observed in the paddy fields of Sivagangai district in Tamil Nadu. The weeds are consumed as vegetables by the local people. During present study, botanical names of the weeds along with their families, vernacular names, mode of consumption and utilities as food have been documented.